Pengaruh Sertifikat Halal, Legalitas Usaha, dan Kualitas Kemasan dalam Membentuk Keputusan Pembelian Konsumen Pada Produk Mixue Dikota Mataram - Hafizi, Muhammad Aziz; Athar, Handry Sudhiarta (Postgraduate, University of Mataram, 2024)
Mixue's presence raises doubts due to uncertainty about its halal status, as it currently lacks the necessary halal certification required in the Indonesian market. This has sparked concerns among consumers, especially given China's majority non-Muslim population. The uncertainty surrounding Mixue's halal status has led to skepticism among a significant portion of the Indonesian population. While some individuals prioritize halal food products, others are indifferent, choosing to buy Mixue products regardless of their halal status. Many consumers feel the need to ensure a product's halal status before making a purchase. This research aims to explore the importance of a Halal Certificate, Business Legality, and Packaging Quality in shaping consumer purchase decisions for Mixue products in Mataram City. The study utilized a sample of 100 respondents who are consumers of Mixue products in Mataram City. The findings reveal that both the Halal certificate and packaging quality have a positive and significant impact on the purchase decisions of Mixue products in Mataram City. However, business legality does not show a positive and significant influence on the purchase decisions of Mixue products in Mataram City. These results indicate that the Halal certificate and packaging quality are effective in enhancing purchase decisions, while business legality has a less pronounced impact on the purchase decisions of Mixue products in Mataram